FORCE MAJEURE SEBAGAI ALASAN WANPRESTASI AKIBAT CORONA VIRUS DISEASE 2019 (COVID-19) DALAM USAHA JASA KONSTRUKSI (Analisis Undang-Undang Nomor 2 Tahun 2017 Tentang Jasa Konstruksi) - Timotius Cham Dennys Maurits Korano Korano (Jurnal Inovasi Penelitian, 2022)
This thesis aims to solve the problem of force majeure research in the construction service business affected by the corona virus disease 2019 (COVID-19) pandemic. In particular, this thesis attempts to explore the application of article 47 paragraph (1) letter j of Law Number 2 of 2017 concerning Construction Services which regulates the circumstances of coercion in its application to construction service businesses affected by the spread of the coronavirus disease 2019 (COVID-19) pandemic. In the a quo article it is not explained in detail what forms a construction service business can be declared to have experienced force majeure, so that the application of this article in a case often creates legal uncertainty. This discussion is important because the spread of the COVID-19 pandemic for the construction service business has created a debate regarding the relevance of implementing coercive circumstances for construction service businesses that are experiencing obstacles in completing their business activities. This research is a normative juridical research through a statutory approach and a case approach. In addition, this study uses a data collection method in the form of literature study. Through this literature study, researchers collect documents and data to be processed using content analysis methods. The results of the study show that the application of force majeure in construction service businesses affected by the COVID-19 pandemic is relevant to be applied. This is in accordance with the classification of the division of force majeure in certain fields, such as relative, subjective, temporary, special, and exclusive. In addition, there are legal consequences of the application of force majeure in the construction service business, namely the temporary termination of contracts, renegotiation, and the provision of compensation to workers in the construction service business.